Chemical Characteristics of Hotong Seeds (Setaria italica) Based on Fermentation Method - Siahaya, Griennasty Clawdya; Pelatta, Chendy Sofianty; Ivakdalam, Lydia M (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
This study aims to describe the chemical characteristics of fermented hotong seeds. The research method used is descriptive exploratory, through testing samples of fermented hotong seeds using two different types of yeast, namely tempeh yeast and band yeast, then a proximate test is carried out. Results: The fermentation process using tape yeast produced a carbohydrate content of 60.8%, protein of 9.98%, fat of 1.47%, ash content of 2.68%, and moisture content of 5.05%. Meanwhile, hotong seed samples fermented with tempe yeast produced a carbohydrate content of 59.1%, protein of 9.91%, fat of 1.47%, ash content of 2.06%, and moisture content of 4.70%. These results illustrate that the fermentation process with tape yeast produces a higher proximate test value for carbohydrate, protein and ash content, on the other hand, fermented hotong beans with tape yeast are lower compared to fermented hotong beans tempeh. The results of this fermentation treatment have a higher proximate test value compared to unfermented control hotong beans. Conclusion: The best treatment from this study is hotong seeds with fermented yeast tape. Suggestion: It is suggested that for future research, it is necessary to design the treatment of fermentation and use a starter of bacteria (BAL) to be able to get different results and statistical tests can be carried out to be able to see meaningful differences between treatments.